2008
DOI: 10.1021/jp8058799
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Wavelength Dependence of Primary Charge Separation in Reaction Centers from Rhodobacter sphaeroides

Abstract: The excitation wavelength dependence of the initial electron transfer rate in both wild type and mutant reaction centers from Rhodobacter sphaeroides has been studied between 840 and 920 nm as a function of temperature (10-295 K). The dynamics of primary charge separation show no resolvable excitation wavelength dependence at room temperature over this spectral range. A small variation in rate with excitation wavelength is observed at cryogenic temperatures. The low temperature results cannot be explained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this model, the initial charge separation is limited by protein dynamics rather than by a static electron transfer barrier, and conformational diffusion occurs until a configuration with a low activation energy for electron transfer is achieved. Subsequent studies on the wavelength dependence (39) and temperature dependence (40) of electron transfer support this model.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this model, the initial charge separation is limited by protein dynamics rather than by a static electron transfer barrier, and conformational diffusion occurs until a configuration with a low activation energy for electron transfer is achieved. Subsequent studies on the wavelength dependence (39) and temperature dependence (40) of electron transfer support this model.…”
Section: Introductionmentioning
confidence: 87%
“…At present, it is difficult to distinguish between these two situations. In view of the reported important role of conformational changes that optimize the electron transfer pathway (38)(39)(40), the fast rate could be interpreted as the intrinsic electron transfer rate in an optimized configuration, with the slower rate delayed by the typical time it takes for the protein to reach a conformation optimal for electron transfer. Heterogeneity in BRC electron transfer rates has been reported before.…”
Section: Heterogeneity In Electron Transfer Ratesmentioning
confidence: 99%
“…However, one might think that such static heterogeneity would also manifest itself in other measurements, such as excitation wavelength dependence of forward electron transfer, yet this is not observed. 31 Further, the systematic variation in the relative contribution of the two components between mutants suggests this kinetic feature is fundamental to the homogeneous function of reaction centers rather than an effect of multiple populations.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…[5][6][7] Time-resolved spectroscopic measurements indicated that the excited electron in (P L P M )* is transferred to H L via B L along the L-branch on a time scale of a few ps. [39][40][41][42][43][44][45][46][47][48][49][50] Despite the pseudo-C 2 symmetric cofactor arrangement, the difference in the amino acid sequences between the L-and M-branches leads to the difference in the redox potentials of the pigments via electrostatic interactions and polarization. [51][52][53] A previous study using time-dependent density functional theory (TDDFT) with the quantum mechanics/molecular mechanics/polarizable continuum model (QM/MM/PCM) method indicated that the intermediate states of charge separation along the L-and M-branches, i.e., [P L P M ]c + B L c À and [P L P M ]c + B M c À , are lower and higher in energy than that of (P L P M )*, respectively.…”
Section: Introductionmentioning
confidence: 99%